A Truncating Variant of CHRNG as a Cause of Escobar Syndrome: A Multiple Pterygium Syndrome Subtype - Sandweiss, Alexander J.; Patel, Shalinkumar; Bader, Mohammad Y.; Kylat, Ranjit I. (Journal of Pediatric Genetics, 2020)
Escobar syndrome is a milder variant of multiple pterygium syndrome characterized by pterygia, scoliosis, and multiple congenital contractures. It is most frequently due to a genetic variant in CHRNG, which encodes the γ-subunit of the nicotinic acetylcholine receptor. Though the subunit is considered a “fetal” form and transitions to the “adult” ε-subunit by 33 weeks' gestation, the pathogenic musculoskeletal effects during fetal development render children with this condition permanently affected. We report a neonate with homozygous CHRNG c.117dupC and discuss some of the downstream clinical effects we observed with this variant.
Keywords: CHRNG; arthrogryposis multiplex congenita; multiple pterygium syndrome; nicotinic acetylcholine receptor